Histochemical and morphological features of biopsied and stripped oocytes from the Brazilian endangered teleost pirapitinga, Brycon nattereri (Characiformes) - Maria, Alexandre N.; Orfao, Laura H.; Rizzo, Elizete; Ninhaus-Silveira, Alexandre [UNESP]; Viveiros, Ana T. M. (Cambridge Univ Press, 2015)
The aim of the present study was to characterize biopsied and stripped oocytes from the Brazilian endangered teleost pirapitinga (Brycon nattereri) using histochemical and morphological analyses. Biopsied oocytes had a mean diameter of 2.225 mm (modal diameter: 2.312 mm), complete vitellogenesis and a central or slightly eccentric nucleus. Neutral polysaccharides were detected in the follicular cells, zona radiata and yolk globules, while acidic polysaccharides were detected in the follicular cells and cortical alveoli. Ten out of the 19 females treated with two doses of carp pituitary extract (cPE) released oocytes, which were also analysed. Stripping occurred 292 +/- 39 degree-hours after the second dose of cPE and led to a mean spawning weight of 36.2 g, 10% spawning index, 241 oocytes/g of ova, 8222 oocytes/female and 23 oocytes/g of body weight. Stripped oocytes had a mean diameter of 2.33 mm and a mode at 2.375 mm, were weakly adhesive and coloration ranged from wine to brown. Under scanning electron microscopy, stripped oocytes exhibited a single funnel-shaped micropyle located at the animal pole and a zona radiata that measured 7.7 m in thickness with eight pore canals/m(2). Oocyte morphology in Brycon nattereri is similar to that found in other species of the genus, except for the larger size and weaker adhesiveness. These findings provide essential information for a better understanding of the reproductive biology of B. nattereri and the establishment of conservation measures for this threatened species.
Keywords: Fish; Oocyte surface; Reproduction; Spawning; Ultrastructure